Study on etiological profile of pleural effusion in tertiary care centre in Dakshin Kannada - Khilar, Neha; S., Sathiqali A. (International Journal of Advances in Medicine, 2023)
Background: Pleural effusion (PE) is a pathological state that often develops in patients with thoracic or systemic diseases and if not diagnosed and treated early, heralds a serious prognosis. Aim of the study was to determine the etiological profile of PE from exudative and transudative pleural fluid. Methods: This cross-sectional study was conducted in participants admitted with PE in the general medicine ward of Yenepoya medical college hospital between the period of January 2021 and December 2021. The patients were analyzed for the socio-demographic characteristics; examination was done with focus on general physical examination, respiratory system, cardiovascular system and gastrointestinal system. SPSS was used for analysis. Results: A total of 80 participants fulfilling inclusion criteria were included in the study. The mean age of participants was 50.28±15.85 years. Among the participants, 36.3% were female and 63.8% were male, with male preponderance in the study. PE, according to Light’s criteria, was differentiated into exudative effusion which accounted for 63.8% and the rest 36.3% were transudative. The most common cause of PE was TB followed by malignancy. The most common malignancy causing effusion was carcinoma of the lung. All the etiologies of PE showed a male preponderance and it was statistically significant (p<0.05). Conclusions: In males, PE was more frequently observed. The main causes of PE were TB and cancer. One of the Clinical indicators including pallor demonstrated a strong correlation with malignant and tuberculous effusions. Malignancy and empyema were substantially correlated with clubbing.